Genetic Association of DLG5 R30Q with Familial and Sporadic Inflammatory Bowel Disease in Men. Issue 5 (2nd June 2013) - Lin, Z.; Poritz, L.; Franke, A.; Li, T.Y.; Ruether, A.; Byrnes, K.A.; Wang, Y.; Gebhard, A.W.; MacNeill, C.; Thomas, N.J.; Wu, R.; Schreiber, S.; et al.
Abstract : Background : The association of DLG5 R30Q with IBD has been replicated in several populations, but is not statistically significant in others. We studied the incidence of DLG5 alleles in a population of IBD patients from Pennsylvania. Methods : DLG5 R30Q (rs1248696) and G1066G (rs1248634) were analyzed with PCR-based RFLP methods in a total of 521 subjects, that included 105 individuals with IBD and 139 without IBD from a familial IBD registry, 107 with sporadic IBD, and 170 unrelated healthy controls. R30Q was further analyzed with SNPlex™ Genotyping System in 473 samples. Results : RFLP genotyping data showed that, DLG5 R30Q was significantly associated with IBD overall ( p =0.006), and separately with CD ( p =0.009) and UC ( p =0.024). The association of R30Q with IBD was entirely due to a male-associated effect (male vs female p =0.015 vs 0.241 (IBD), p =0.024 vs 0.190 (CD), and p =0.019 vs 0.575 (UC)). The frequency of the A allele carriage was elevated in both affected and unaffected members in the familial IBD cohort compared to healthy controls ( p =0.037). In the family pedigrees, we observed differences in the expression of IBD in individuals carrying the A allele between families. Conclusions : In the studied population, DLG5 R30Q was associated with all forms of IBD. An elevated presence of the R30Q variant was observed in all members of a familial IBD registry. This association of the R30Q variant with IBD was male-specific.